2020
DOI: 10.3390/ma13194417
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Field in the Heat Transfer Process of PEEK Thermoplastic Composite Fiber Placement

Abstract: Under the effect of different process parameters, the temperature field inside the thermoplastic fiber is very complex and directly affects the fusion quality between the resins. Considering the heat transfer behavior of thermoplastic fiber polyether ether ketone (PEEK) as the research object, a mathematical model of heat transfer in the thermoplastic composite fiber placement with the relevant boundary conditions was established. Ansys Parametric Design Language (APDL) was used to generate the finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The authors suggested a line speed of 5 mm/s, hot gas temperature of 750 • C and tool temperature of 145 • C for the first layer. The suggested parameters were similar to those recommended by Cao et al [67]. In addition, Liu et al also recommended using a Teflon tape to protect the rubber compaction roller for the AFP process [66].…”
Section: Studies On Factors Affecting In Situ Consolidation Qualitysupporting
confidence: 62%
See 2 more Smart Citations
“…The authors suggested a line speed of 5 mm/s, hot gas temperature of 750 • C and tool temperature of 145 • C for the first layer. The suggested parameters were similar to those recommended by Cao et al [67]. In addition, Liu et al also recommended using a Teflon tape to protect the rubber compaction roller for the AFP process [66].…”
Section: Studies On Factors Affecting In Situ Consolidation Qualitysupporting
confidence: 62%
“…For the modeling of ISC using forced convection heaters such as hot gas torch, many researchers used constant heat coefficient values (h heater ) to model the heat transfer between the heater and the FRTP material [66][67][68]. Tafreshi et al discussed the determination of the h heater value for ISC using hot gas torch using two approaches, namely (i) calculating h heater from the Nusselt number and the Reynold number based on impinging jet theories, and (ii) obtaining h heater by considering the energy absorbed by the material and then fitting numerical calculations to experimental data [45].…”
Section: Modeling Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a simulation of laser processing drilling was conducted to minimize slag and splash formation. The temperature distribution of the carbon steel during laser processing was investigated by varying the processing parameters and the heat transfer mechanisms during laser drilling, and the impact of the temperature distribution and various laser processing parameters on the laser drilling process was also assessed [17,18]. This work can help avoid excessive slag and splash in practical production scenarios, providing valuable guidance on the application of laser drilling processing techniques.…”
Section: Introductionmentioning
confidence: 99%